The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1210/en.2007-0327
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Phytoestrogens in the Perinatal Period Affects Androgen Secretion by Testicular Leydig Cells in the Adult Rat

Abstract: The use of soy-based products in the diet of infants has raised concerns regarding the reproductive toxicity of genistein and daidzein, the predominant isoflavones in soybeans with estrogenic activity. Time-bred Long-Evans dams were fed diets containing 0, 5, 50, 500, or 1000 ppm of soy isoflavones from gestational d 12 until weaning at d 21 postpartum. Male rats in all groups were fed soy-free diets from postnatal d 21 until 90 d of age. The mean +/- SD concentration of unconjugated (i.e. biologically active)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
4
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 62 publications
8
46
4
4
Order By: Relevance
“…The levels of genistein affecting steroidogenic enzyme activity in the present study approximate levels that have been measured in individuals consuming soy products [7]. The present results are in agreement with our previous findings of genistein acting directly in rat Leydig cells to cause inhibition of androgen biosynthesis [8,9]. Changes in androgen biosynthesis, occasioned by exposure to endocrine disruptors, have the potential to interfere with androgen-stimulated reproductive tract development [19,20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The levels of genistein affecting steroidogenic enzyme activity in the present study approximate levels that have been measured in individuals consuming soy products [7]. The present results are in agreement with our previous findings of genistein acting directly in rat Leydig cells to cause inhibition of androgen biosynthesis [8,9]. Changes in androgen biosynthesis, occasioned by exposure to endocrine disruptors, have the potential to interfere with androgen-stimulated reproductive tract development [19,20].…”
Section: Discussionsupporting
confidence: 92%
“…These findings, along with previous observations indicating that genistein interferes with LH signalling in rat Leydig cells [8,9], suggest that genistein exerts multiple mechanisms to affect testicular steroidogenesis. LH binding stimulates steroidogenic enzyme activity, which enhances androgen biosynthesis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Male rats were given different concentrations of soy isoflavones from gestational day 12 until weaning at day 21 postpartum. The results showed that low dose increased serum and cultured Leydig cell testosterone levels and high doses decreased serum testosterone production at day 21 postpartum [8]. Recent studies have shown that highdose soy isoflavones administered to rats from prenatal life to sexual maturity induced changes in the morphology of the seminiferous epithelium and significantly decreased testicular testosterone concentration.…”
Section: Brief Communication (Original)mentioning
confidence: 94%
“…In animal studies, correlations have already been made between phytoestrogen intake, androgen decrease and ED. 37,[65][66][67] In the light of this evidence, it is important to bridge the lacunae in the understanding of this sexual health threat to men through well-designed epidemiological and prevalence studies.…”
Section: Oestrogenic Provocation From the Environmentmentioning
confidence: 99%